Emocionálna a sociálna inteligencia vo vzťahu k zvládaniu v ranej adolescencii - Baumgartner, F. (František); Zacharová, Z. (2011)
This paper presents results regarding the relationship between emotional and social intelligence and coping strategies. Emotional intelligence was assessed as ability (Situational Test of Emotional Understanding) and as a personality trait (Trait EI questionnaire-Adolescent Short Form). Social intelligence, as a similar concept to EI, was examined by Tromsø Social Intelligence Scale (TSIS). Coping strategies were measured by using the Children’s Coping Strategies Checklist (Ayers, et al., 1999). The research sample consisted of 104 children at an early age of adolescence. Our results revealed some significant relationships between emotional intelligence and coping strategies. The distinctiveness of both constructs of EI was manifested.